Perancangan Interior Jakarta Creative Hub Bergaya Urban Pop-Art - Daffa Farras Dienputra; Erina Wiyono (Journal of Innovative and Creativity, 2025)
This design is based on the rampant public interest in the science of the creative industry. However, the community's enthusiasm is not directly proportional to the facilities to accommodate creative industry activities. One of the facilities that can be developed to accommodate these activities is a co-working space. Jakarta itself has a co-working space that can be used for activities. However, there are still many people who do not know this facility, so the Jakarta Creative Hub as a government asset cannot develop further. This design uses a qualitative approach with a case study method, where data is obtained from user observations in similar places. Through these problems, Jakarta Creative Hub will be relocated to Arkadia Green Park which is easier to reach and designed with the concept of growing space and collaborative area in urban pop-art style to facilitate and accommodate people who need space to create and work.